The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1476-4598-12-20
|View full text |Cite
|
Sign up to set email alerts
|

Molecular features in arsenic-induced lung tumors

Abstract: Arsenic is a well-known human carcinogen, which potentially affects ~160 million people worldwide via exposure to unsafe levels in drinking water. Lungs are one of the main target organs for arsenic-related carcinogenesis. These tumors exhibit particular features, such as squamous cell-type specificity and high incidence among never smokers. Arsenic-induced malignant transformation is mainly related to the biotransformation process intended for the metabolic clearing of the carcinogen, which results in specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 108 publications
4
63
0
1
Order By: Relevance
“…In North America lung cancer, is one of the leading causes of mortality. Arsenic's capability of inducing specific alterations into pathways that regulate tumor formation in lung cells has been elucidated by Hubaux and colleagues (Hubaux et al, 2013) (Figure 14). Increased exposure of arsenic concomitantly increased the susceptibility of lung cancer both in smokers and non-smokers (Järup and Pershagen, 1991).…”
Section: Lungsmentioning
confidence: 97%
See 1 more Smart Citation
“…In North America lung cancer, is one of the leading causes of mortality. Arsenic's capability of inducing specific alterations into pathways that regulate tumor formation in lung cells has been elucidated by Hubaux and colleagues (Hubaux et al, 2013) (Figure 14). Increased exposure of arsenic concomitantly increased the susceptibility of lung cancer both in smokers and non-smokers (Järup and Pershagen, 1991).…”
Section: Lungsmentioning
confidence: 97%
“…Various studies showed the susceptibility of human lungs towards arsenic consumption (Celik et al, 2008;Gibb et al, 2011;Guha Mazumder, 2007) and managed to setup a link between ingestion of iAs through drinking water and human lung cancer development (Ferreccio et al, 2000). Nevertheless, lungs are one of the major targets for tumorigenesis due to arsenic exposure (Hubaux et al, 2013). High mortality rate of patients due to lung cancer has been reported (Hopenhayn-Rich et al, 1998;Lamm et al, 2013;Smith et al, 2012b).…”
Section: Lungsmentioning
confidence: 98%
“…However, recent studies have shown that arsenosugars, the major arsenical constituent of marine algae [9], can be easily metabolised by humans into a multitude of arsenic metabolites, including dimethylarsinic acid (DMA) and its sulphur analogue, thio-DMA, which have been extensively toxicologically characterised [10,11]. Considerable progress has been made in recent years to address arsenic toxicity, including both genetic and epigenetic alteration [12,13]. In spite of these efforts, the putative mechanism underlying arsenic toxicity remains vague given the complicated metabolism of arsenic in the human body, and no effective treatment for arsenicosis exists [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the same period, the Antofagasta region (North of Chile), historically exposed to high levels of drinking water Arsenic (dw-As), showed a mortality rate of 31.6 for both genders, with a rate of 44.2 and 17.4, for men and women, respectively [4][5][6][7][8]. The implementation of earlydetection technologies and prognostic biomarkers are imperative, specifically in cities highly exposed to environmental carcinogens, such as PAHs and Arsenic [9][10][11][12][13]. It is extremely important to have complementary and noninvasive tools, to apply in asymptomatic population, especially to individuals with high risk of LC.…”
Section: Introductionmentioning
confidence: 99%